¿Se vulnera el mismo deber en un delito de infracción de un deber que en un delito especial de deber? El caso del delito de administración desleal o fraudulenta - Chinguel Rivera, Alejandro Ignacio (2025)
This article analyses the structure of so-called crimes related to breaches of duty and special crimes of duty. It specifically aims to understand the foundation of duty that forms this structure. To achieve this, the research focuses on the various concepts of “positive duty” that underpin the classification of a crime as either a violation of duty or a special duty. The goal is to demonstrate the significance of establishing a duty as positive. We will also explore how attributing criminal responsibility in certain economic crimes, such as unfair or fraudulent administration, relies on this foundation.